Trends and Markets in Liquefied Natural Gas - Shepherd, Rob (World Bank, Washington, DC, 2012)
"It was the best of times, it was the worst of times, it was the age of wisdom, it was the age of foolishness, it was the epoch of belief, it was the epoch of incredulity, it was the season of Light, it was the season of Darkness, it was the spring of hope, it was the winter of despair, we had everything before us, we had nothing before us . . ." Quoting the opening of Charles Dickens's Tale of Two Cities in connection with the current state of the liquefied natural gas (LNG) industry may, if anything, be overly optimistic, beset as the industry is with low prices and stuttering demand in its Asian stronghold. But it is hard to resist calling on these contrasts to characterize the LNG industry, for despite its problems, there are glimmerings of change that could profoundly improve its lot. LNG is essentially a niche fuel. Liquefying and shipping gas is expensive, so the LNG route is attractive for developers only where there is no local market or where capacity in the local market is insufficient to take all the available local supplies. LNG requires large investments by the buyers in terminal and regasification facilities, so it generally flourishes only where there is a shortage of indigenous gas supplies and where competition from pipeline gas is limited. In bulk, LNG is suitable for transport only by sea, so its use in landlocked areas is confined to small peak shaving plants or isolated locations such as central Australia.